Trade Reforms, Labor Regulations, and Labor-Demand Elasticities: Empirical Evidence from India - Hasan, Rana; Mitra, Devashish; Ramaswamy, K.V (The Review of Economics and Statistics, 2007)
Using industry-level data disaggregated by states, this paper finds a positive impact of trade liberalization on (the absolute values of) labor demand elasticities in the Indian manufacturing sector. The magnitudes of these elasticities turn out to be negatively related to protection levels that vary across industries and over time. Furthermore, we find that these elasticities are not only larger in size for Indian states with more flexible labor regulations, they are also impacted there to a larger degree by trade reforms. Finally, we find that the reforms have led to a reduction in the share of labor in total output and value added, possibly due to the reduction in the bargaining power of workers.